DEI QuickTips Infograph - El-Gebali, Sara (My University, 2021)
A practical guide with tips and advice on creating safe, inclusive spaces with intersectionality in mind. For more information, please visit https://www.opencider.org/
Keywords: guide; diversity; intersectionality